(untitled) (World Bulletin of Social Sciences, 2025)
In this article cultural differences and technical term translation problems are discussed. Simultaneously, the challenges of interpreting words and cross-cultural relationships are analyzed. Intercultural differences, or how other cultures affect language and what errors can occur during translation, are covered in the article. It specifically looks at how various cultural settings, language-based traditions and practices, worldviews, and social norms impact the competence of the translator. Mistakes in translation frequently result in issues like unclear meaning, disregard for cultural quirks, or improper usage of non-linguistically and culturally specific words. The article also stresses the importance of taking the translator’s cultural sensitivity, localization, and adaptation into account. It has been demonstrated that in order to address these issues, translators must have a thorough awareness of cultural variations, adhere to linguistic nuances, and include the appropriate contextual remarks.